Odpowiedź:
1) -a-b
2)-6x-4y+7a= 7a-6x-4y
3) -5a+3b+7c
4) -3a+6x+24t
5)[tex]-4a^{2}[/tex]+4ax+8axy
6) (rozumiem jako [tex]m^{2} , m^{3}[/tex])
[tex]5m^{2} +5m^{3}+ 5m^{4}[/tex]
7)10a-2x
8) -3a+6ab+4a+8b
9)ax-ay-2b+bx
10)2a-5ay-6ay-24y=2a-11ay-24y
11)[tex]3a^{2}[/tex]+3ay+4ay+[tex]4y^{2}[/tex]= [tex]3a^{2}[/tex]+7ay+[tex]4y^{2}[/tex]
12)[tex]6x^{2}+15xy-14xy-35y^{2}= 6^{2} +xy-35y^{2}[/tex]
13)[tex]18a^{2}-12ab-48ab+32b^{2}+12ab=18a^{2} -48ab+32b^{2}[/tex]
14) 14m-7-5m-3= 9m-10
15) [tex]x^{2} -8ax-x^{2}-9ax= -17ax[/tex]
16) 8a-56+4a+20+6a-6= 18a-42
17)1+4x-3-5x= -2-x
18)0,8a+1,2a-0,4b-2a+0,3b+0,1b= 0,8a+1,2a-2a-0,4b+0,3b+0,1b=0